(untitled) (Swiss Medical Weekly, 2025)
This position paper on the detection of atrial fibrillation after ischaemic stroke is a statement of the “Heart and Brain” committee of the Swiss Stroke Society. This position paper summarises present knowledge on the detection of atrial fibrillation after ischaemic stroke or transient ischaemic attack. An interdisciplinary standard for monitoring on the stroke unit and after discharge is proposed respecting recent developments and Swiss particularities. The main evolution in the field is that the role of atrial fibrillation screening after stroke or transient ischaemic attack has shifted from understanding the index stroke to preventing the next stroke; it therefore should also be performed in patients with certain other stroke aetiologies, e.g. symptomatic carotid artery stenosis. The duration of atrial fibrillation monitoring should be based on an individualised risk assessment incorporating clinical characteristics as well as cardiac and laboratory biomarkers. Given the paucity of randomised controlled data on this topic, this position paper intends to give practical advice to healthcare professionals involved in stroke care in Switzerland based on a consensus between experts in the field.